Analysis of technical implementation officer satisfaction of activities on the performance of local contractors on road and bridge projects in Sarmi regency - Rachman, Ivan Hairil Pratama; Julison, Bernathius; Rante, Harmonis (Jurnal Info Sains : Informatika dan Sains, 2024)
With the increase in construction development, the demand for construction services is increasing with the demand that the results of construction work are of high quality. Quality construction work results must certainly be supported by the readiness of supporting factors, namely management factors, financial factors, human resource factors, work experience factors, supporting facilities and infrastructure factors and equipment readiness factors. So that a construction project can be said to be successful if it is able to meet its objectives, namely: completed at the planned time, in accordance with the allocated costs and meet the required quality. The location of the research was carried out on road and bridge construction work managed by the Public Works and Spatial Planning Office in Sarmi Papua.